Political Parties as a Factor in the Postmodernism - Dimitriev, Emil (Institute of Knowledge Management, 2023)
Abstract: The evolution of political thought during the period of post-industrial society raises a number of discussions about the projection in which policy will move as activity and science. No matter what it has long shown features that profile its ‘’ timelessness’’. Strongly based in Aristotle definition of man as a social being, upgraded with new worldviews initiated along an evolutionary or revolutionary path, it creates symbiosis with human survival. However, as in other areas and in politics, futuristic views form a diapasone of different views,on whose ultimate edges are the positions that are on the line of claim that the policy profile will survive for a long time in the form which the world knows. And the other extreme standpoint which in its essence has the change and proclaimed "the era" of the end of ideologies, as one of the main features of politics. Numerous projections for the evolution of politics have been positioned between these two extremes, which have created some differences between themselves. In this context, political parties as one of the main elements of politics are subject to the interest of political and sociological science, in which direction their evolution will go. Given that the parties are a major factor in operationalizing politics, their profile becomes a determinant of future political activities. Globalization as an irreversible process strongly affects the transformation of political communities, forcing the model of interculturalism on global and multiculturalism on regional and local level. Special interest for analysis is the profile of political parties in post-communist countries, in multiethnic environments, in countries integrated or not into international organizations. On national level, the profile of political parties in Macedonia is a special example of maintaining a gap between declared and real politics. As far as the independence of our country and the legal normative arrangement of our community we have declared a civil and multiethnic society. A society that in the terms of liberal democracy would create the Macedonian model of multiethnic pluralism, in response to the old single-mindness that failed to form a demos in full splendour but maintained ethnos in full capacity. The paradox of modern Macedonian society consists of the fact that all political parties, especially parliamentary, accept the civil, ie the multiethnic character of the country, and even after three decades of democracy, still dominate parties built on ethnic basis. Even part of the parties are politically limited to geographical part of the country. This placement of the parties complemented with frequent nationalist rhetoric is the major factor that affects destructively to the social cohesion and the building of the multicultural society based of equal opportunities.
Keywords: politics, state, political parties, ideology.